Lack of Significant Effects of Chlamydia trachomatis Infection on Cervical Adenocarcinoma Risk: Nested Case-Control Study. - Vitaly Smelov; Tarik Gheit; Karin Sundström; Alexander Ploner; Sandrine McKay-Chopin; Carina Eklund; Massimo Tommasino; Joakim Dillner (PLoS ONE)
Background A role of Chlamydia trachomatis in HPV-induced cervical carcinogenesis has been reported for cervical cancer but studies on cervical adenocarcinoma are limited. Methods A total of 1,553 cervical smears taken up to 26 years before diagnosis in a large population-based nested case-control study of cervical adenocarcinoma (AC, 132 cases with matched controls), and adenocarcinoma in situ (AIS, 159 cases with matched controls) were tested for C. trachomatis and HPV DNA by a type-specific PCR bead-based multiplex genotyping (TS-MPG) assay. Results Only 1.7% of samples were positive for C. trachomatis, with no significant differences between AC/AIS cases and controls. HPV-positivity was detected in 49.3% of C. trachomatis-negative and 65.4% C. trachomatis-positive samples, respectively. Conclusions A large prospective study did not find any risk for cervical adenocarcinoma and/or AIS conferred by C. trachomatis infection. Impact C. trachomatis appears not to be involved in cervical adenocarcinomas.